1996
DOI: 10.1111/j.1460-9592.1996.tb00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral midazolam premedication for paediatric day case patients

Abstract: Forty-nine children having day-stay surgical procedures were randomly assigned to receive oral midazolam 0.75 mg.kg-1 or placebo in a double blind fashion. The child's level of anxiety was assessed before premedication using parental, child and observer scales. The child and observer anxiety scores were repeated in the anaesthetic room. Most children presented for anaesthesia in a calm state, irrespective of whether they had received midazolam. Parents tended to overestimate their child's level of anxiety. Obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 21 publications
(17 reference statements)
4
35
2
2
Order By: Relevance
“…1 In anaesthetic applications in paediatric patients, oral midazolam is reported in a wide range of 0.2-1 mg kg À1 . 15 Day et al 16 reported that in the high-anxiety level group aged 2.9 AE 1.6 a dose of 0.2-0.3 mg kg À1 and in the age group 5 AE 1 a dose of 0.5-0.7 mg kg À1 midazolam is appropriate for sedative premedication. In the second group of our study, 0.7 mg kg À1 midazolam was applied.…”
Section: Discussionmentioning
confidence: 98%
“…1 In anaesthetic applications in paediatric patients, oral midazolam is reported in a wide range of 0.2-1 mg kg À1 . 15 Day et al 16 reported that in the high-anxiety level group aged 2.9 AE 1.6 a dose of 0.2-0.3 mg kg À1 and in the age group 5 AE 1 a dose of 0.5-0.7 mg kg À1 midazolam is appropriate for sedative premedication. In the second group of our study, 0.7 mg kg À1 midazolam was applied.…”
Section: Discussionmentioning
confidence: 98%
“…(10) and Cray et al . (13). With regard to mask acceptance, our results (77–83%) are similar to those of Karl et al .…”
Section: Discussionmentioning
confidence: 99%
“…The oral administration of midazolam is widely used for this purpose because of its rapid onset, short duration of action, and lack of significant side effects [1][2][3][4]. However, previous studies have shown contradictory effects of oral midazolam premedication on the quality of recovery from sevoflurane-induced anesthesia [5][6][7].…”
Section: Introductionmentioning
confidence: 99%